2014
DOI: 10.1371/journal.pntd.0003288
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Contribution of Hosts with Different Parasite Concentrations to the Transmission of Visceral Leishmaniasis in Ethiopia

Abstract: BackgroundAn important factor influencing the transmission dynamics of vector-borne diseases is the contribution of hosts with different parasitemia (no. of parasites per ml of blood) to the infected vector population. Today, estimation of this contribution is often impractical since it relies exclusively on limited-scale xenodiagnostic or artificial feeding experiments (i.e., measuring the proportion of vectors that become infected after feeding on infected blood/host).MethodologyWe developed a novel mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 39 publications
1
45
1
Order By: Relevance
“…L. infantum (Pourabbas et al, 2013;Mary et al, 2006;Moral et al, 2002;Biglino et al, 2010), and L. donovani (Miller et al, 2014; have been detected in blood in up to 58% of asymptomatic infections by a cross-sectional study. 14% of 4,695 asymptomatic Ethiopians were qPCR-positive in blood of which 3.2% had high genome equivalent counts (Miller et al, 2014), suggesting that distribution of parasitaemias is skewed and that perhaps the small proportion of asymptomatic infections with higher parasitaemia are more likely to develop disease and have a disproportional role in onward transmission. However of 44 Brazilian children with positive qPCR results at baseline, only 10 remained qPCR-positive 12 months later, showing a significant decrease in genome counts (dos Santos Marques et al, 2012).…”
Section: Transmission: Xenodiagnosis Vs Tissue and Blood Parasite Loadsmentioning
confidence: 98%
See 2 more Smart Citations
“…L. infantum (Pourabbas et al, 2013;Mary et al, 2006;Moral et al, 2002;Biglino et al, 2010), and L. donovani (Miller et al, 2014; have been detected in blood in up to 58% of asymptomatic infections by a cross-sectional study. 14% of 4,695 asymptomatic Ethiopians were qPCR-positive in blood of which 3.2% had high genome equivalent counts (Miller et al, 2014), suggesting that distribution of parasitaemias is skewed and that perhaps the small proportion of asymptomatic infections with higher parasitaemia are more likely to develop disease and have a disproportional role in onward transmission. However of 44 Brazilian children with positive qPCR results at baseline, only 10 remained qPCR-positive 12 months later, showing a significant decrease in genome counts (dos Santos Marques et al, 2012).…”
Section: Transmission: Xenodiagnosis Vs Tissue and Blood Parasite Loadsmentioning
confidence: 98%
“…kDNA for preparing qPCR standards) varies between amastigotes and promastigotes, and even between strains . Studies suggest that there exists a parasite density threshold above which canine and human infections are disproportionately infectious (Courtenay et al, 2014;Miller et al, 2014). In contrast, natural wildlife hosts (e.g.…”
Section: Transmission: Xenodiagnosis Vs Tissue and Blood Parasite Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that diagnostic tests can distinguish more infectious dogs, which are the actual sources of infection under natural conditions, from less infectious or non-infectious dogs. An elegant study in Ethiopia showed that in fact only a few individuals contribute to transmission 30 . A control program that discriminates infectiousness would identify such animals.…”
mentioning
confidence: 99%
“…Identifying the hosts that contribute most to the infection of vectors population is crucial for understanding the transmission dynamics of vector borne diseases, as well as for planning intervention strategies targeting the relevant infected host groups [16]. The parasitemia is an important factor of the host reservoir competence on vector borne pathogens, influencing their contribution (host infectiousness profile) to the infected vector population [17]. The Giemsa-stained blood smears is a conventional method used to determine parasitemia in clinically infected cattle, but this test has low analytical sensitivity and is ineffective in carrier animals [15,18,19].…”
Section: Introductionmentioning
confidence: 99%